Gaussian Filtering Method to Remove Noise in Images - Satya, I Dewa Gede Rama; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021, 2021)
Capturing every moment is not taboo in this era. One way to capture the moment is to use a photo, but the results are often unsatisfactory. Noise, is one of the many causes of unsatisfactory results. Noise is a disturbance caused by digital data storage received by the image data receiver which can interfere with image quality. Noise can be caused by physical (optical) disturbances in the image capturing device, such as dust on the camera lens or due to improper processing. To get rid of this noise, you can use various methods, of which Gaussian Filtering is one of them. In this research, we will implement it using Matlab. The type of file used is a photo that has a jpg format and has noise above 75%. After doing image processing, it shows the results of the image which initially has noise and after the image quality improvement process is carried out, the image quality is clearer and the noise decreases.